Open-case series of a remote administration and group setting comprehensive behavioral intervention for tics (RG-CBIT): A pilot trial - Inoue, Takeshi; Togashi, Kohei; Iwanami, Jumpei; Woods, Douglas W.; Sakuta, Ryoichi (Frontiers in Psychiatry, 2022)
Purpose The comprehensive behavioral intervention for tics (CBIT) is the first-line psychotherapeutic treatment for individuals with tic disorders. However, most patients with tic disorders do not have access to CBIT due to different factors including lack of trained therapists, treatment cost, and travel distance. Such barriers are more prominent in non-English speaking countries. Therefore, the current study assessed the preliminary efficacy, feasibility, and acceptability of remotely administered group CBIT (RG-CBIT) in Japan. Method This was an open-case series that adopted the AB design. Three Japanese children aged between 6 and 13 years who were diagnosed with TS were recruited. RG-CBIT was developed based on the published CBIT manual. Videoconference application, slide presentation software, and cloud learning platform were used as appropriate. Results The Yale Global Tic Severity Scale scores of all participants decreased from baseline to post-treatment. That is, the score reduced by an average of 7.0. Regarding feasibility and acceptability, the attendance rate of participants was 100%, and the process measurement items had favorable scores. Conclusions RG-CBIT had satisfactory efficacy, feasibility, and acceptability. Hence, it could mitigate the barriers for treatment access.